Truncating erythropoietin receptor rearrangements in acute lymphoblastic leukemia - Iacobucci, Ilaria (Cancer Cell, 2016)
Chromosomal rearrangements are a hallmark of acute lymphoblastic leukemia (ALL) and are important ALL initiating events. We describe four different rearrangements of the erythropoietin receptor gene EPOR in Philadelphia chromosome-like (Ph-like) ALL. All of these rearrangements result in truncation of the cytoplasmic tail of EPOR at residues similar to those mutated in primary familial congenital polycythemia, with preservation of the proximal tyrosine essential for receptor activation and loss of distal regulatory residues. This resulted in deregulated EPOR expression, hypersensitivity to erythropoietin stimulation, and heightened JAK-STAT activation. Expression of truncated EPOR in mouse B-cell progenitors induced ALL in vivo. Human leukemic cells with EPOR rearrangements were sensitive to JAK-STAT inhibition, suggesting a therapeutic option in high-risk ALL.